The Comparison Between Students of Coeducational Schools and Single-Sex School in Malaysia - Azhari, Ahmad Husam Bin; Akil, Nadia Amira Binti Mohd; Aidi, Dinie Syazwani Binti Badrul; Shah, Fatin Usyairah Binti Mohd; Anuar, Sharifah Miza Farhana Binti Said; Ujang, Suriyati (SCAD Independent, 2023)
The study aimed to determine which type of school appeared to be better because it has been a concern for parents when choosing schools for their children. The study also compared pupils’ socio-emotional, peer victimization, extracurricular achievements, academic performance, and career aspirations in three types of schools in Kuantan, Pahang. Data from three different schools were collected using a single cross-sectional with probability sampling design and analyzed using R programming. The result showed that pupils in girls’ schools performed better in mathematics and science than in boys’ and coeducational schools. Furthermore, pupils in boys’ schools were more interested in extracurricular activities than in coeducational schools. However, it was found that pupils in girls’ schools were more inspired to determine their future careers as compared to pupils in boys’ schools. Therefore, the study concluded that single-sex school was better regarding academic performance, career aspiration, peer victimization, and extracurricular activities. The study results suggest that students or parents choose the best path or school for their future endeavors.